Metformin combined with insulin aspart for ameliorating blood glucose levels and maternal and neonatal outcomes in women with gestational diabetes mellitus and chronic hypertension - Wang, Wei (Am J Transl Res, 2021)
Objective: To investigate the effect of metformin combined with insulin aspart on blood glucose levels and maternal and neonatal outcomes in women with gestational diabetes mellitus (GDM) accompanied by chronic hypertension (CH). Methods: A prospective study was conducted on 112 women with GDM and CH. The patients were divided into the control group and the observation group according to a random number table method, with 56 patients in each group. The control group received injections of insulin aspart based on blood pressure control, and the observation group received injections of insulin aspart combined with oral metformin based on blood pressure control. Besides, blood glucose levels, maternal pregnancy outcomes and neonatal complications before and after intervention were compared between the two groups. Results: Before intervention, there was no significant difference in blood glucose and blood pressure levels between the two groups (P > 0.05). After intervention, the observation group showed significantly decreased fasting blood glucose, 2-h postprandial plasma glucose and glycosylated hemoglobin levels than the control group (P < 0.05); the blood pressure in the observation group was significantly lower as compared with that before intervention (P < 0.05). Additionally, the incidences of adverse pregnancy outcomes (e.g., premature rupture of membranes) and neonatal jaundice and macrosomia were significantly lower in the observation group than in the control group after intervention (both P < 0.05). Conclusion: Metformin combined with insulin aspart for treating GDM and CH can effectively control blood glucose and blood pressure levels and reduce the risk of adverse perinatal and neonatal outcomes, which exerts positive effect in clinical treatment.